ПІДГОТОВКА МАЙБУТНІХ ПЕДАГОГІВ ДО СПІЛКУВАННЯ (Педагогіка вищої та середньої школи, 2022)
The article deals with the significance of pedagogical intercourse as an important component o f future teachers' professional and pedagogical training.